Energy loss through the steam trap in a steam system - Mohd Hanif, Ab Hamid (2010)
This thesis is about the energy loss through the steam trap in the steam system. In industry, steam traps frequently fail but they are not noticed except when they are leaking. If steam trap fail in failed open, live steam can escape to surrounding. High amount of energy will loss from the steam system. It takes weeks or months before it being repaired or replaced. The first objective of this study is to measure the heat loss for normal thermodynamic steam trap in respond to operating pressure for different condensate load. The second objective is to measure the heat loss for failed open thermodynamic steam trap in respond to operating pressure for different condensate load. The last objective is to compare energy loss between normal and failed open steam trap. From the last objective, the actual energy loss if failed steam trap is not repaired is determined. Thermodynamic steam trap has been tested in the experiment and the operating pressure is below 1 bar. Condensate that discharges from steam trap is collected to record the reading of its temperature and weight. These data is used to determine the energy loss through the steam trap. For normal steam trap, energy loss for high condensate load is higher than low condensate load. For failed open steam trap, energy loss for high condensate load is lower than low condensate load. Finally, after comparing the result, steam system that has low condensate load has higher energy loss compare to high condensate load.